2004
DOI: 10.1021/ja047677x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of meta Electron-Donating Groups on the Electronic Structure of Substituted Phenyl Nitrenium Ions

Abstract: Density functional theory (UB3LYP/6-31G(d,p)) was used to determine substituent effects on the singlet-triplet-state energy gap for 21 meta-substituted phenylnitrenium ions. It was found that strongly electron-donating substituents stabilize the triplet state relative to the singlet state. With sufficiently strong meta electron donors (e.g., m,m'-diaminophenylnitrenium ion) the triplet is predicted to be the ground state. Analysis of equilibrium geometries, Kohn-Sham orbital distributions, and Mulliken spin de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
32
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 83 publications
3
32
0
Order By: Relevance
“…Strongly electron-donating substituents in the meta position increase the value of the DE st , and with sufficiently strong donors, ground state triplets are predicted. 35 The small energy gaps that arise with meta donors can be traced to a change in the electronic configuration of the triplet state nitrenium ions. When the meta substituent becomes sufficiently electron donating, the triplet state can be described as a diradical cation formally resulting from an internal electron transfer from the substituent orbital to the nitrenium ion center (Fig.…”
mentioning
confidence: 99%
“…Strongly electron-donating substituents in the meta position increase the value of the DE st , and with sufficiently strong donors, ground state triplets are predicted. 35 The small energy gaps that arise with meta donors can be traced to a change in the electronic configuration of the triplet state nitrenium ions. When the meta substituent becomes sufficiently electron donating, the triplet state can be described as a diradical cation formally resulting from an internal electron transfer from the substituent orbital to the nitrenium ion center (Fig.…”
mentioning
confidence: 99%
“…[7] Winter, Falvey, and Cramer reported that strongly electron-donating substituents at the m positions result in a (p,p*)-type triplet ground state in phenylnitrenium ions. [8] Our preliminary calculations have shown that OCA predicts correct trends of the band shifts for derivatives of phenylnitrene (2) with electronically weak substituents, but the OCA-based model is broken when a robust substituent such as a nitro group is introduced, as will be reported in a forthcoming publication. .…”
mentioning
confidence: 77%
“…[2d, [6][7][8] Excited electronic states of high-spin nitrenes and carbenes have been documented for only a few systems, and all of the theoretical studies deal with triplet-state mononitrenes [9,10] or monocarbenes. [11] Disclosing the nature of the excited electronic states of high-spin molecular entities seems an important issue from the viewpoint of materials science.…”
mentioning
confidence: 99%
“…Although both singlet (S 0 ) and triplet (T 1 ) states of 1 exist, experiments and calculations [40][41][42][43][44][45][46][47] agree that the singlet is, with few exceptions, 37,38,46,47 the ground state due to donation of electron density from the p-orbitals of the aromatic ring into the empty p-orbital of the presumably planar nitrenium center. The triplet is accessible via triplet-sensitized photolysis, 33,37,38 but most chemistry that has been examined is due to singlet 1.…”
mentioning
confidence: 89%